The metabolic function of pyruvate kinase M2 regulates reactive oxygen species production and microbial killing by neutrophils - O'Neill, Luke (My University, 2023)
Neutrophils rely predominantly on glycolytic metabolism for their biological functions, including reactive oxygen species (ROS) production. Although pyruvate kinase M2 (PKM2) is a glycolytic enzyme known to be involved in metabolic reprogramming and gene transcription in many immune cell types, its role in neutrophils remains poorly understood. Here, we report that PKM2 regulates ROS production and microbial killing by neutrophils. Zymosan-activated neutrophils showed increased cytoplasmic expression of PKM2. Pharmacological inhibition or genetic deficiency of PKM2 in neutrophils reduced ROS production and Staphylococcus aureus killing in vitro. In addition, this also resulted in phosphoenolpyruvate (PEP) accumulation and decreased dihydroxyacetone phosphate (DHAP) production, which is required for de novo synthesis of diacylglycerol (DAG) from glycolysis. In vivo, PKM2 deficiency in myeloid cells impaired the control of infection with Staphylococcus aureus. Our results fill the gap in the current knowledge of the importance of lower glycolysis for ROS production in neutrophils, highlighting the role of PKM2 in regulating the DHAP and DAG synthesis to promote ROS production in neutrophils
PUBLISHED
Keywords: Neutrophils; glycolytic metabolism; reactive oxygen species (ROS); Neutrophils; glycolytic metabolism; reactive oxygen species (ROS)